2021
DOI: 10.1093/plphys/kiab143
|View full text |Cite
|
Sign up to set email alerts
|

Isolating an active and inactive CACTA transposon from lettuce color mutants and characterizing their family

Abstract: Dietary flavonoids play an important role in human nutrition and health. Flavonoid biosynthesis genes have recently been identified in lettuce (Lactuca sativa); however, few mutants have been characterized. We now report the causative mutations in Green Super Lettuce (GSL), a natural light green mutant derived from the red line NAR; and GSL-Dark Green (GSL-DG), an olive-green natural derivative of GSL. GSL harbors CACTA 1 (LsC1), a 3.9 kb active non-autonomous CACTA superfamily transposon inserted in the 5’ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…The TEs account for 74.2% of the lettuce genome (Reyes- Chin-Wo et al, 2017). Thus, transposons may play an important role in the evolution of lettuce (Gurdon et al, 2021;Yu et al, 2020). In this study, we found that a CACTA transposon was inserted into the 3 0 -UTR of LsGLK and that this insertion led to the development of pale-green leaves.…”
Section: Alternative Splicing Triggered By Transposons Contributes To Phenotypic Variationmentioning
confidence: 59%
See 1 more Smart Citation
“…The TEs account for 74.2% of the lettuce genome (Reyes- Chin-Wo et al, 2017). Thus, transposons may play an important role in the evolution of lettuce (Gurdon et al, 2021;Yu et al, 2020). In this study, we found that a CACTA transposon was inserted into the 3 0 -UTR of LsGLK and that this insertion led to the development of pale-green leaves.…”
Section: Alternative Splicing Triggered By Transposons Contributes To Phenotypic Variationmentioning
confidence: 59%
“…The red color of lettuce has been well characterized. At least four polymorphic genes associated with red leaves were identified (Gurdon et al, 2021;Su et al, 2020;Zhang et al, 2017). The variations in the green color of lettuce leaves were preliminarily studied.…”
Section: Introductionmentioning
confidence: 99%
“…One of the QTLs for the content of chlorophyll (qLG4.1) was previously detected in multiple mapping populations (Kwon et al, 2013;Simko et al, 2016;Mamo et al, 2019;Parra et al, 2021, Simko et al, unpublished results), while the other three QTLs appeared to be located at the genomic regions not previously associated with the content of chlorophyll. Out of 12 QTLs for the content of anthocyanins, 7 (qRLC2.1, RLL3, RLL2, qRLC5.2, qRLC7.2, RLL4, and ANS) were found at or near QTLs and genes for red leaf color or anthocyanin content detected in previous studies (Kwon et al, 2013;Mamo et al, 2019;Gurdon et al, 2021;Simko et al, 2022b, Simko et al, unpublished results, Zhang et al, 2017Su et al, 2020;Wei et al, 2021;Wada et al, 2022), while the remaining five QTLs were new.…”
Section: Phenotypic Relationship Of Pigments Plant Development and Th...mentioning
confidence: 73%
“…In recent years, INSV has emerged as a primary threat to the lettuce industry in the Western United States (Hasegawa and Del Kwon et al, 2013;Simko et al, 2016;Mamo et al, 2019;Parra et al, 2021, Simko et al, unpublished Kwon et al, 2013;Mamo et al, 2019;Gurdon et al, 2021;Simko et al, 2022b, Simko et al, unpublished results, Zhang et al, 2017Su et al, 2020;Wei et al, 2021;Wada et al, 2022) a If a QTL detected in the current study is located in the same or an adjacent bin as a QTL/gene detected in previous studies, it gets the same name as the previously detected QTL/gene. Pozo-Valdivia, 2022;Hasegawa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…CACTA transposons are one of the most abundant superfamilies of DNA transposons (Tian, 2006;Wicker et al, 2007;Sergeeva et al, 2010;Lisch, 2013;Belyayev et al, 2022). It has been reported that CACTA transposons constitute c. 2-15% of plant genomes (Paterson et al, 2009;Vogel et al, 2010;Gurdon et al, 2021;Z. Y. Wang et al, 2022).…”
Section: The Multifaceted Effects Of Cacta Transposons In Gene Functionsmentioning
confidence: 99%